TEXT STRUCTURE IN CULINARY GUIDES WINE AND DINE: SINGAPORE’S TOP RESTAURANTS - Ni Putu Tetania Ari Kusumadewi (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2021)
Abstract. This study aims to find the stages and language features of the descriptive text structure in Wine & Dine: Singapore's Top Restaurants. The contribution of this research is that it can be used as a reference in the preparation of descriptive texts that will have social functions as information reports on the topic of restaurants. The theory used in this study is the theory of Descriptive Text by Knapp and Watkins (2005). This research method uses qualitative methods. This research data is the descriptive text in the culinary guidebook. The research found that the topic of data is a restaurant and there are 12 (twelve) stages in the restaurant descriptive text that are Food, Identity, Decoration, Services, Location, Facilities, Comment, Beverages, Branches, Abstract, Price, Employees. The language features used in restaurant descriptive text are the use of simple present tense, relational verbs, action verbs, adjectives, and adverbs. This research concludes that although 12 (twelve) stages have been found in the restaurant descriptive text, the stages used are 3-6 stages in the composition of the descriptive text. Relational verbs and action verbs are not applied to all sentences in one text. Adjectives are used more often than Adverb or Adverbial phrases in restaurant descriptive text.